General Legal Characteristic and Classification of Crimes Committed in the Sphere of Small and Medium Business - ZHARYLKAPOVA, Gulzagira; ABDUKARIMOVA, Zhanar; KALKANOVA, Zhanna; KARAYEVA, Aibala (Journal of Advanced Research in Law and Economics, 2018)
The paper is devoted to the legal regulation in the legislation of the Republic of Kazakhstan and foreign legislations of the issues of criminal liability for the commission of criminal offenses in the sphere of small and medium business. The relevance of this topic, as well as the importance of foreign experience in this area for the Kazakhstani legislator during the period of deep national economic restructuring, is unquestionable. The purpose of the work set by the author is to find the ways to improve the provisions of criminology, the theory of criminal law, criminal legislation and regulations on small and medium business. The work uses the provisions of criminology, criminal and financial law, as well as the data of official statistics and sociological research published in the media. The author identified the system of criminal legal norms aimed at combating economic crimes, carried out an analysis of classifications of economic criminal offenses in the legislation of the Republic of Kazakhstan, taking into account criminal law norms and criminological characteristics, studied the issues of the differentiation of criminal liability for economic crimes, prepared proposals on the improvement of existing theoretical provisions of criminology and criminal law in combating economic crimes in small and medium business, taking into account the legislative practice of developed countries, the provisions of foreign and domestic theoretical and law enforcement practice.